2009
DOI: 10.1055/s-0029-1241735
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro-Brain Natriuretic Peptide as a Biomarker for Hypertensive Disorders of Pregnancy

Abstract: We tested the hypothesis that the cardiac biomarker N-terminal pro-brain natriuretic peptide would be elevated in hypertensive disorders of pregnancy, with an increase in levels of this biomarker across increasing gradations of disease severity. We performed a case-controlled study of women admitted to labor and delivery at the Hospital of the University of Pennsylvania between 24 and 42 weeks of gestation. Cases had hypertension that developed after 20 weeks of gestation, and controls were normotensive women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Recent studies have confirmed that BNP concentrations are elevated in PE and other hypertensive disorders of pregnancy 19-22. The increased serum BNP levels in PE are greater than that documented in normotensive pregnancies,23,24 suggesting that BNP activation in PE is a response to changes in the maternal circulation that reflect the pathophysiological changes in the utero–placental unit.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have confirmed that BNP concentrations are elevated in PE and other hypertensive disorders of pregnancy 19-22. The increased serum BNP levels in PE are greater than that documented in normotensive pregnancies,23,24 suggesting that BNP activation in PE is a response to changes in the maternal circulation that reflect the pathophysiological changes in the utero–placental unit.…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that N‐terminal pro‐brain natriuretic peptide (NT‐pro‐BNP) may be closely associated with cardiovascular damage, as it reflects ventricular function . It has also been demonstrated that the NT‐pro‐BNP levels of women with severe preeclampsia is significantly higher than that of women with uncomplicated pregnancies …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PE is a risk factor for future cardiovascular disease. In particular, N‐terminal pro‐B natriuretic peptide (NT‐proBNP), which is released from cardiac myocytes in response to myocardial stretch or ischemia and is used as a biomarker of chronic heart failure in non‐obstetric populations, is present at higher concentrations in women with PE. In pregnancies complicated by PE, there appears to be a graded increase in natriuretic peptide levels with increasing severity of the disease, which may predict cardiovascular complications.…”
Section: Introductionmentioning
confidence: 99%